Superconductivity of topological insulator Sb2Te3−ySey under pressure. (22nd September 2021) - Taguchi, Tomoya; Ikeda, Mitsuki; Li, Huan; Suzuki, Ai; Yang, Xiaofan; Ishii, Hirofumi; Liao, Yen-Fa; Ota, Hiromi; Goto, Hidenori; Eguchi, Ritsuko; Kubozono, Yoshihiro
Abstract: The crystal structures of Sb2 Te3− y Se y ( y = 0.6 and y = 1.2) at 0–24 GPa were investigated by synchrotron x-ray diffraction. The stoichiometry of Sb2 Te3− y Se y used in this study was determined to be Sb2 Te2.19(9) Se0.7(2) for y = 0.6 and Sb2 Te1.7(1) Se1.3(3) for y = 1.2, on the basis of energy-dispersive x-ray spectroscopy. The sample of Sb2 Te2.19(9) Se0.7(2) showed a structural phase transition from a rhombohedral structure (space group No. 166, R 3 ¯ m ) (phase I) to a monoclinic structure (space group No. 12, C 2/ m ) (phase II), with increasing pressure up to ∼9 GPa. A new structural phase (phase II′) emerged at 17.7 GPa, a monoclinic structure with the space group C 2/ c (No. 15). Finally, a 9/10-fold monoclinic structure (space group No. 12, C 2/ m ) (phase III) was observed at 21.8 GPa. In contrast, the sample of Sb2 Te1.7(1) Se1.3(3) provided only phase I (space group No. 166, R 3 ¯ m ) and phase II (space group No. 12, C 2/ m ), showing one structural phase transition from 0–19.5 GPa. These samples were not superconductors at ambient pressure, but superconductivity suddenly appeared with increasing pressure. Superconductivity with superconducting transition temperatures ( T c 's) of 2 and 4 K was observed above 6 GPa in phase I of Sb2 Te2.19(9) Se0.7(2) . In this sample, the T c values of 6 and 9 K were observed in phase II and phase II′ or III of Sb2 Te2.19(9) Se0.7(2), respectively. Superconductivity with T c 's of 4 and 5 K suddenly emerged in Sb2 Te1.7(1) Se1.3(3) at 13.6 GPa, which corresponds to phase II, and it evolved to 6.0 K under further increased pressure. A T c value of 9 K was finally found above 15 GPa. The magnetic field dependence of T c in phase II of Sb2 Te2.19(9) Se0.7(2) and Sb2 Te1.7(1) Se1.3(3) followed a p -wave polar model, suggesting topologically nontrivial superconductivity.